2013
DOI: 10.1158/0008-5472.can-12-3655
|View full text |Cite
|
Sign up to set email alerts
|

DDB2: A Novel Regulator of NF-κB and Breast Tumor Invasion

Abstract: The DNA repair protein damaged DNA-binding 2 (DDB2) has been implicated in promoting cell-cycle progression by regulating gene expression. DDB2 is selectively overexpressed in breast tumor cells that are noninvasive, but not in those that are invasive. We found that its overexpression in invasive human breast tumor cells limited their motility and invasiveness in vitro and blocked their ability to colonize lungs in vivo, defining a new function for DDB2 in malignant progression. DDB2 overexpression attenuated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 29 publications
3
59
0
1
Order By: Relevance
“…Interestingly, a putative DDB2 binding element TCCCCTAA, which is one nucleotide different from the ones found in NFKBIA (15) or NEDD4L (14), is located between the fragments P2 and P3. The available PAM motif in the region around that DDB2-cognate element and CRISPR/Cas9 genome editing technique allowed us to generate two HT-29 cell lines that harbor deletions of 132bp (between P2 and P3) and 416bp (partially overlapping with P2 and P3) (Figs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, a putative DDB2 binding element TCCCCTAA, which is one nucleotide different from the ones found in NFKBIA (15) or NEDD4L (14), is located between the fragments P2 and P3. The available PAM motif in the region around that DDB2-cognate element and CRISPR/Cas9 genome editing technique allowed us to generate two HT-29 cell lines that harbor deletions of 132bp (between P2 and P3) and 416bp (partially overlapping with P2 and P3) (Figs.…”
Section: Resultsmentioning
confidence: 94%
“…DDB2 associates with the promoter region of its target genes, including SOD2, NFKBIA and NEDD4L (1315). To study whether DDB2 also associates with the Rnf43 promoter, Chromatin immunoprecipitation (ChIP) assays were conducted in HCT116 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is a structurally conserved family of dimeric transcription factors that plays pivotal roles in maintaining an invasive phenotype as well as promoting carcinogenesis (30). It also plays a central role in EMT through direct activation of the transcription of Snail, which has been established as a critical mediator of EMT (31).…”
Section: Discussionmentioning
confidence: 99%
“…Besides DDB2 could promote cellular apoptosis through subduing the levels of Bcl-2 [25,26] and p21 in cells harboring irreparable DNA damage [21,27]. DDB2 could also inhibit colon neoplasm metastasis [28] and limit the invasiveness and motility of invasive human breast tumor cells through controlling NF-κB activity [29], as well as mediating senescence [29]. Furthermore, new studies found that DDB2 overexpression caused a reduction of the cancer stem cells population related to repress the oncogenicity of ovarian cancer cells, nevertheless the knockdown of DDB2 caused an expansion of the cancer stem cells population [30].…”
Section: Introductionmentioning
confidence: 99%